Memory-work - Haug, Frigga (Psyke & Logos, 2023)
Memory work is a method for feminist social research. It combines the advantages of consciousness raising groups with the strength of theoretical analysis. It is in fact work with one 's own memory guided by theory. Thus it is a challenge for the personalities involved. It allowes to overcome the gap between researchers and their objects of research and in the same time gives a history and a language, a scientific concern to all those lives and experiences of numerous women, for their everyday lives. The article of memory work, which by now is used by a number of female research groups in Germany, deals with the problem of language, of single case studies and the right of generalization; the problem of subjectivity, identity and ideology etc. It is a call for working in collectives and gives some hints how everybody could start working with her own memory. Memory work is a method which has to be improved while in practice. Thus it is a challenge for all of us: for researchers, women in the movement, psychologists or those who are interested in therapeutical advice.